Fuel cell and its curve characteristics - Muzamir, Isa; Che Mat, Hadzer; Ismail, Daut; Faizah Abu, Bakar (Institut Teknologi Bandung (ITB), 2008)
Organized by Institut Teknologi Bandung (ITB), 29th - 30th November 2006 at ITB Bandung, Indonesia.